Macroeconomic Variables and Jakarta Islamic Index (JII) in Indonesia: an Approach of Error Correction Model - Dian Wahyudi; Abdul Qoyum (Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Kalijaga, 2022)
The purpose of this study is to examine the impact of macroeconomic variables on the Jakarta Islamic Index (JII) over the period 2012-2021. Macroeconomic variables include inflation, the exchange rate, the bi-rate, global oil prices, and the price of gold. In this study, the Error Correction Model (ECM) was used to examine the short- and long-term impact of macroeconomic variables on the di Jakarta Islamic Index (JII). According to the findings, the Indonesian sharia exchange rate and Bi-Rate had an impact on the sharia stock index in the short run. In contrast, interest rates, global oil prices, and global gold prices have a long-term impact on the sharia stock index. Variable inflation has no effect on either.